Relationship between Student Activities in KSR PMI Organization with Learning Achievement in Universitas Negeri Padang - Gusma Yudasmi; Tasril Bartin (Universitas Negeri Padang, 2019)
This research is motivated by the low student achievement in the KSR PMI organization at UNP, this is alleged because it has to do with student activities in the KSR PMI organization at UNP. The purpose of this study is to describe: (1) student activities in the KSR PMI organization at UNP, (2) student achievement in the KSR PMI organization at UNP, and (3) the relationship between student activities in the KSR PMI organization and learning achievement at UNP. This study is a correlational study with a population of KSR PMI members at UNP totaling 195 people. The sampling technique used in this study uses a stratified sampling technique. The population that will be sampled in this study is 30% of the population of 195 people, namely 58 members. Instrument and its development by preparing a questionnaire. Data analysis techniques using the percentage frequency and product moment. The results of the study stated that: (1) student activities in the KSR PMI organization at UNP is categorized good, (2) student achievement in the KSR PMI organization at UNP is categorized as poor, (3) there was a significant relationship between student activities in KSR PMI organization with learning achievements at UNP. Based on the results of the study it is recommended that students be able to balance activities both within the organization and in lectures and be able to maintain and improve their learning achievement at the KSR PMI UNP unit.Keywords: Activities, Learning Achievement